Pro-fashion Trivialization of Academic Researches: Mission Metamorphosing to Mockery - Atindra Dahal (JINEA: Journal of Innovation in Education and Learning, 2026)
Research excellence and graph are popularly fashioned as well as deeply demanded attributes in almost every sector. Among others, it stands as no second priority or obsession- on any alibi or ground- to the professionals engaged in academic peregrination or galaxy/fraternity of higher education facilitators/resource persons. Most academicians opt to engage and present a tone of accruing confidence on commanding research skills followed with maintaining smart publication portfolio. Having number of publications and receiving wider citation responses are inherently presumed as an added charisma. Quite often, the same is deemed as core academic strength and pronouncedly ranked token of merit. Minus it, a bogeyman trap of incompetence is created and unethically extended too.  However, the paper debunks the purported research culture and critiques the countless contemporary practices being exercised in name of research only as hugely hogwash attempts. Here, this paper boldly argues that most activities currently advancing in name of research are aligned to multifold mockeries, utter travesty than committed mission at all. Research attempts have been a cheap and light fashion instead, recently.